Hyperthyroidism Complicated with Diabetes Mellitus Under the Health Promotion Model: Changes in Thyroid Hormones, Glucose-Lipid Metabolism, and Inflammatory Markers - Tang, Miao; Xu, Jiao; Chen, Yanling; Zhou, Bo (Journal of Medical Biochemistry, 2025)
Objective: To investigate the effects of a Health Promotion Model (HPM)-based comprehensive intervention on thyroid hormones, glucose-lipid metabolism, and inflammatory markers in patients with hyperthyroidism (HT) complicated by diabetes mellitus (DM), and to elucidate the potential mechanisms underlying these effects. Methods: A total of 142 patients diagnosed with HT and DM between January 2024 and January 2025 were enrolled. Participants were divided into two groups: the HPM group (n=64), which received a structured HPM-based intervention, and the conventional group (n=78), which underwent standard management. Laboratory assessments were conducted before and after the intervention to evaluate thyroid hormones (FT3, FT4, TSH), glucose-lipid metabolism parameters (fasting plasma glucose [FPG], glycated hemoglobin [HbA1c], total cholesterol [TC], triglycerides [TG]), inflammatory markers (high-sensitivity C-reactive protein [hs-CRP], interleukin-1β/6 [IL-1β/IL-6]), and bone metabolism indicators (osteocalcin [BGP], alkaline phosphatase [ALP], calcitonin [CT]). Data were analyzed using SPSS 24.0. Results: Compared to the conventional group, the HPM group exhibited significantly greater improvements in thyroid function, with more pronounced reductions in FT3 and FT4 (P<0.05) and a greater increase in TSH (P<0.05). Regarding glucose-lipid metabolism, significantly larger decreases in FPG, HbA1c, TC, and TG were identified in the HPM group (P<0.05). Among inflammatory markers, the HPM group showed significant reductions in hs-CRP, IL-1β, IL-6, MIP-1α, and MMP-9 (P<0.05), whereas the conventional group only exhibited improvements in hs-CRP and IL-1β (P<0.05). No significant intergroup differences were observed in bone metabolism parameters (BGP, ALP, CT; P>0.05). Conclusion: The HPM-based intervention, through cognitive restructuring, behavioral modification, and environmental support, effectively enhanced thyroid function, ameliorated glucose-lipid metabolic disturbances, and mitigated chronic inflammation in patients with HT and DM.